THE IMPACT OF A KUD-ORIENTED PEDAGOGICAL APPROACH ON STUDENTS’ MASTERY OF FUNDAMENTAL HANDBALL TECHNIQUES - Basil Ahmed Ali; Asst. Prof. Dr. Hussam Abed Muh (Proximus Journal Publishing, 2025)
The overarching objective of this scholarly inquiry is to formulate pedagogical frameworks grounded in the KUD ( Knowledge , Understand , Doing ) instructional strategy, with the aim of cultivating a repertoire of foundational handball skills among students. The study also seeks to evaluate the effectiveness of these meticulously designed instructional paradigms in enhancing the assimilation of critical motor proficiencies. To this end, the researchers adopted an experimental approach, organizing the investigation around two cohorts—experimental and control—each subjected to pre- and post-intervention assessments, a methodology deemed optimally suited to the research’s nature and aims
Keywords: Kud Strategy; Fundamental Skills; Handball